Drought and surface‐level solar radiation predict the severity of outbreaks of a widespread defoliating insect. Issue 8 (13th August 2018) - Haynes, Kyle J.; Tardif, Jacques C.; Parry, Dylan
Abstract: Defoliating insects are a major factor impacting tree growth in temperate and boreal forests, but the effects of climate change on the severity and frequency of outbreaks of these insects are not well understood. Dendrochronological reconstruction of forest tent caterpillar ( Malacosoma disstria ) outbreaks on trembling aspen ( Populus tremuloides ) in southwestern Manitoba, Canada, from 1851 to 2010 was used to examine the effects of changes in temperature, incident surface‐level solar radiation, and drought severity on the cyclicity, frequency, and severity of outbreaks. Outbreak severity was determined by comparing the tree‐ring widths of trembling aspen with those of white spruce ( Picea glauca ), which is not a forest tent caterpillar host. Wavelet analysis suggested the cyclicity of outbreaks increased after 1930. From 1930 to 2010, the dominant period length of outbreak cycles steadily increased over time from three to seven years, coinciding with long‐term declines in drought severity. The strength of forest tent caterpillar suppression of trembling aspen growth in a given year was inversely related to incident solar radiation and drought severity during late spring (the larval feeding period) of the same year. The effect of late spring drought on the impact of forest tent caterpillar on ring growth differed from that of summer drought. There was a nonlinear relationship between growth suppression in a given year and summer drought severity in the previous year; slightly above‐average drought severity was associated with reduced impacts of the defoliator, whereas severe drought was associated with intense growth suppression. Strong suppression of aspen growth observed during outbreaks from 1983 to 2010 may be partly explained by observed long‐term trends of decreasing atmospheric transmittance of solar radiation (a phenomenon termed "global dimming") and increasing soil moisture availability during late spring. However, as the severity and frequency of summer droughts are expected to increase over the 21st century, the nonlinear relationship between summer drought severity and growth suppression the following year suggests a future in which summer droughts precede severe outbreaks that threaten the health of boreal forest hardwood trees.